2014
DOI: 10.1007/s10600-014-1183-6
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents, Phenolic Compounds, and Antioxidant Activity of Crataegus azarolus Leaves and Flowers Growing in Algeria

Abstract: Hawthorn (Crataegus spp.), belonging to the Rosaceae family, is rich in sugars, minerals, and vitamins A and C. The fruits and flowers of many hawthorn varieties are well known as a heart tonic, have hypotensive effects, and are considered to be generally safe and well tolerated [1]. Previous investigations indicate that Chinese Crataegus extracts have beneficial effects, e.g., anti-inflammatory [2], hypolipidemic [3], and antioxidant [4]. Other proprieties have also been elucidated such as anticarcinogenic [5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…The main groups of detected volatiles were acids and esters (12 compounds) 27.5% for HD-MW, 50.7% for HD; alkanes and alkenes (17 components) comprised 40.8 % for HD-MW, 29.5% for HD. It is obvious that the latter group of compounds obtained by using HD-MW method is quite similar to our results [12]. The Algerian C. azarolus aerial parts were also investigated by Boudjada et al, five volatile compounds were identified; 2,4-bis (1,1-dimethyl ethyl)-phenol, tridecanoic acid 12-methyl-methyl ester, pentadecanoic acid 14-methyl-methyl ester, 8-octadecanoic acid methyl ester, and isobutyl nonyl phthalate [13].…”
Section: Resultssupporting
confidence: 90%
“…The main groups of detected volatiles were acids and esters (12 compounds) 27.5% for HD-MW, 50.7% for HD; alkanes and alkenes (17 components) comprised 40.8 % for HD-MW, 29.5% for HD. It is obvious that the latter group of compounds obtained by using HD-MW method is quite similar to our results [12]. The Algerian C. azarolus aerial parts were also investigated by Boudjada et al, five volatile compounds were identified; 2,4-bis (1,1-dimethyl ethyl)-phenol, tridecanoic acid 12-methyl-methyl ester, pentadecanoic acid 14-methyl-methyl ester, 8-octadecanoic acid methyl ester, and isobutyl nonyl phthalate [13].…”
Section: Resultssupporting
confidence: 90%
“…In the literature, there are essential oil studies of Crategus orientalis collected from different regions and isolated from different parts, but there is almost no information about its biological activities such as antioxidant, and antibacterial. It has been reported that palmitic acid, α-farnesene, hexyl benzoate and linoleic acid are valuable antioxidant bioactive components in Crataegus azarolus (Lakache et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation of the antioxidant power :by the free radical scavenging method (dpph) showed that the essential oils studied have good antioxidant activity, especially for the oil extracted by HD having presented an IC 50 of (13,07 ± 0,169) mg / ml, while BHT and Ascorbic acid,showed very potent and effective anti-free radical activity with IC 50 of the order of (19,54 ± 0,32) ) µg / ml and (1,17 ± 0,05) µg / ml respectively. According to Amiri (2010) and Lakache et al (2016), in the free-radical-scavenging activity, the high phenolics and avonoïds contents in C.sinensis essential oils can explain its high free radical scavenging capacity. It has been recognized that phenolics and avonoïds contents of plants, can increase cellular defenses and diminished malignant transformation of cells.…”
Section: Discussionmentioning
confidence: 99%